Separator for secondary battery and electrochemical element comprising same

By placing a heat-resistant adhesive layer containing inorganic particles and specific forms of organic particles on a porous substrate, the shortcomings of the ceramic coating separator in terms of electrode adhesion, adhesion resistance and breathability are solved, and the battery is realized High stability and safety.

CN222530730UActive Publication Date: 2025-02-25SK INNOVATION CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202420542183.9
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Priority Date
2023-03-20
Filing Date
2024-03-20
Publication Date
2025-02-25
Estimated Expiration
2034-03-20

AI Technical Summary

Technical Problem

The existing ceramic-coated separators have shortcomings in electrode adhesion, adhesion resistance and breathability, resulting in poor stability of batteries at high temperatures and easy safety problems such as electrode short circuits and fires.

Method used

A porous substrate having a thickness of 3 to 50 μm, and a heat-resistant adhesive layer is arranged on at least one side thereof, the adhesive layer comprises inorganic particles and organic particles having a plurality of protrusions and valleys, with an average particle size D50. from 0.1 to 1.5 μm.

Benefits of technology

It has achieved excellent electrode adhesion, adhesion resistance and breathability under thin thickness, improved the stability and safety of the battery, and avoided problems such as electrode short circuit and fire.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222530730U_ABST
    Figure CN222530730U_ABST
Patent Text Reader

Abstract

The utility model relates to a diaphragm for a secondary battery and an electrochemical element comprising the diaphragm for the secondary battery. According to one implementation example, there may be provided a separator for a secondary battery, comprising: a porous substrate having a thickness of 3 to 50 [mu] m; and a heat-resistant adhesive layer that is disposed on at least one surface of the porous base material and has a thickness of more than 0 [mu] m and 2 [mu] m or less, the heat-resistant adhesive layer containing: inorganic particles; and a binder component containing organic particles having a plurality of protrusions and a plurality of valleys, the organic particles having an average diameter D50 of 0.1 to 1.5 [mu] m. The diaphragm for the secondary battery and the electrochemical element comprising the diaphragm for the secondary battery have excellent electrode adhesiveness, adhesion resistance and air permeability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model relates to a secondary battery separator and an electrochemical element including the same, and more particularly to a secondary battery separator having excellent electrode adhesion, anti-adhesion and air permeability and an electrochemical element including the same. Background Art

[0002] In order to solve the high temperature stability problem of the separator, a ceramic coated separator (CCS) with a porous inorganic particle layer formed on one or both sides of a porous substrate has been used in the past. The ceramic coated separator has the advantage of excellent heat resistance due to its low high temperature heat shrinkage rate, so it is suitable for large battery systems for EVs.

[0003] However, the ceramic coating separators in the past had insufficient adhesion to the electrodes, so the separators and electrodes often separated during the battery cell assembly process, resulting in distortion and deformation of the electrode assembly. That is, as mentioned above, when the adhesion between the ceramic coating of the separator and the electrode is insufficient, misalignment occurs between the electrode and the separator in the jellyroll during cell stacking. When driving a stacked cell battery with misalignment as described above, local resistance occurs due to misalignment, or physical damage caused by continued use leads to a short circuit between the electrodes, so there are safety issues such as fire.

[0004] Therefore, improving the adhesion between the ceramic coating separator and the electrode is an issue that must be improved for battery stability.

[0005] One method of improving the adhesion between the separator and the electrode is to form an adhesive organic layer on the inorganic particle layer of the ceramic coating separator. However, the air permeability is reduced due to the organic layer, making it difficult to form a thin film, and the electrode adhesion is still poor. In addition, when the separator is wound, the adhesive organic layer is separated from the electrode. Therefore, there are still problems that need to be solved, such as the reduction of the ionic conductivity of the separator and / or the occurrence of thickness deviation when aligning the electrode assembly, thereby hindering the performance of the battery.

[0006] [Prior art literature]

[0007] [Patent Literature]

[0008] (Patent Document 1) Japanese Patent Publication No. 4414165 (Publication Date: 2005.03.03) Summary of the invention

[0009] Technical issues

[0010] In order to solve the above problems, an embodiment of the present invention aims to provide a separator having excellent electrode adhesion, anti-adhesion and air permeability even at a thin thickness, and an electrochemical element including the separator.

[0011] According to one aspect, a diaphragm having a heat-resistant adhesive layer thickness of less than 5 μm and a total diaphragm thickness of less than 20 μm or less than 15 μm can be provided, with the aim of providing a diaphragm having excellent electrode adhesion, anti-adhesion and air permeability within the said range and an electrochemical element comprising the diaphragm.

[0012] Technical Solution

[0013] As a solution for achieving the above-mentioned purpose, the utility model provides a secondary battery separator, comprising: a porous substrate having a thickness of 3 to 50 μm; and a heat-resistant adhesive layer disposed on at least one side of the porous substrate and having a thickness of more than 0 μm and less than 2 μm;

[0014] The heat-resistant adhesive layer includes: inorganic particles; and an adhesive component including organic particles having a plurality of protrusion parts and a plurality of valley parts, wherein an average diameter D50 of the organic particles is 0.1 to 1.5 μm.

[0015] In one implementation example, the heat-resistant adhesive layer may contain 50 wt % or more of the organic particles based on the total weight of the adhesive component.

[0016] In one implementation example, the heat-resistant adhesive layer may further include an organic adhesive as the adhesive component.

[0017] In an implementation example, the organic binder may include any one or more selected from the group consisting of acrylic polymers, silane compounds, styrene butadiene rubber, carboxymethyl cellulose, polyvinylidene fluoride, polyvinyl pyrrolidone, and polyvinyl acetate.

[0018] In an implementation example, the heat-resistant adhesive layer may include 30 to 85 wt % of inorganic particles, 10 to 60 wt % of organic particles, and 1 to 15 wt % of an organic binder, based on the total weight of the heat-resistant adhesive layer.

[0019] In an implementation example, the ratio of the average particle size (D50) of the organic particles to the average particle size (D50) of the inorganic particles may be 0.5 to 2.5 or 0.5 to 1.5.

[0020] In one implementation example, the particle size distribution D10 / D90 of the organic particles may be 0.3 to 0.9.

[0021] In one implementation example, the glass transition temperature (Tg) of the organic particles may be 50 to 90°C.

[0022] In one implementation example, the thickness of the heat-resistant adhesive layer may be greater than 0 μm and less than 5 μm.

[0023] In one implementation example, the organic particles may be secondary particles in which primary particles are mutually agglomerated by surface melting to form a plurality of protrusion parts and a plurality of valley parts, or primary particles having a plurality of protrusion parts and a plurality of valley parts on the surface.

[0024] In one implementation example, the electrode adhesion of the secondary battery separator can be 1.5 gf / 15 mm to 4.0 gf / 15 mm, wherein the electrode adhesion is measured by stacking the secondary battery separator on a carbon sheet (TOYO Tanso Korea, PF-20HP) with a thickness of 200 μm and making the heat-resistant adhesive layer of the secondary battery separator face the carbon sheet, and then bonding it with a hot press at 80°C and 20 MPa for 30 seconds, and then peeling (peeling) 180° using INSTRON's UTM equipment according to ASTM D 903.

[0025] In one implementation example, the air permeability change ΔG of the secondary battery separator measured by the following formula may be 100 seconds / 100 cc or less.

[0026] △G=G1-G2

[0027] In the above formula, G1 is the Gurley permeability of a secondary battery separator having heat-resistant adhesive layers laminated on both sides of a porous substrate, and G2 is the Gurley permeability of the porous substrate itself. The Gurley permeability is measured using a Densometer from Toyoseiki Co., Ltd. according to ASTM D 726, and the unit is seconds / 100cc.

[0028] In one implementation example, the secondary battery separator can be a secondary battery separator in which two secondary battery separators are arranged with the adhesive layers facing each other, and then pressed at a temperature of 60°C and a pressure of 7.5 MPa for 1 hour. When peeled 180° according to ASTM D 903, the adhesive layers do not adhere to each other and are partially or completely peeled off, but are separated in their original state without adhesion.

[0029] Furthermore, as another solution for achieving the above-mentioned object, according to an implementation example of the present invention, an electrochemical element including the secondary battery separator of the above-mentioned implementation example can be provided.

[0030] Technical Effects

[0031] The separator of the utility model can also have excellent electrode adhesion, anti-adhesion or air permeability at a thin thickness.

[0032] The electrode adhesion of the separator of one implementation example may be 1.5 gf / 15 mm or more, 2.0 gf / 15 mm or more, 2.3 gf / 15 mm or more, 2.5 gf / 15 mm or more, 3.0 gf / 15 mm or more, or 1.5 gf / 15 mm to 4.0 gf / 15 mm, wherein the electrode adhesion is measured by laminating the separator on a carbon sheet having a thickness of 200 μm and making the adhesive layer of the separator face the carbon sheet, and then pressing and bonding with a hot press at 80°C and 20 MPa for 30 seconds, and then peeling 180° using a UTM device according to ASTM D 903. According to the implementation example, sufficient electrode adhesion can be ensured even in the case of a relatively small amount of organic particles in the form of secondary particles in which the surface of the primary particles of the polymer having a high glass transition temperature is melted and condensed.

[0033] A separator of an implementation example can ensure excellent electrode adhesion even at a thin thickness, and can have excellent anti-adhesion properties. For example, after two separators with a porous substrate and a heat-resistant adhesive layer are stacked and configured so that the adhesive layers face each other, they are pressed at a temperature of 60°C and a pressure of 7.5MPa for 1 hour. After that, the bonded part is peeled off, and SEM is used to confirm whether the adhesive layer is partially or completely peeled off to cause adhesion between the surfaces of the separators. In this case, adhesion does not occur as a phenomenon in which the adhesive layer is partially detached from each other's separators, that is, it can have excellent anti-adhesion performance.

[0034] A diaphragm of an implementation example can have excellent air permeability even if it has a multilayer structure in which a heat-resistant adhesive layer is arranged on a porous substrate, and the air permeability change (△G) expressed by the following formula can be less than 100 seconds / 100cc, less than 95 seconds / 100cc, or less than 90 seconds / 100cc.

[0035] △G=G1-G2

[0036] In the above formula, G1 is the Gurley permeability of the separator with heat-resistant adhesive layers laminated on both sides of the porous substrate, and G2 is the Gurley permeability of the porous substrate itself. The Gurley permeability is measured using a Densometer of Toyoseiki Company according to ASTM D 726 specifications, and the unit is seconds / 100cc. In addition, the above air permeability change can also be satisfied in the case of a separator with an inorganic particle layer and an adhesive layer laminated in sequence on one side of the porous substrate.

[0037] The separator of one implementation example may be excellent in two or more of electrode adhesion, anti-adhesion and air permeability, and more preferably, may be excellent in electrode adhesion, anti-adhesion and air permeability.

[0038] The separator of a specific implementation example may be excellent in two or more of electrode adhesion, anti-adhesion and air permeability. The separator of a more specific implementation example may be excellent in electrode adhesion, anti-adhesion and air permeability. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 is a photograph of the morphology of organic particles according to one aspect of the present invention observed by SEM;

[0040] Figure 2 The morphology of organic particles according to one aspect of the present invention is shown;

[0041] Figure 3 This is a photograph of the heat-resistant adhesive layer of the separator of Example 1 observed by SEM;

[0042] Figure 4 This is a photograph of the heat-resistant adhesive layer of the separator of Comparative Example 1 observed by SEM;

[0043] Figure 5 This is a photograph of the heat-resistant adhesive layer of the separator of Comparative Example 2 observed by SEM;

[0044] Figure 6 This is a photograph of the heat-resistant adhesive layer of the separator of Comparative Example 3 observed by SEM;

[0045] Figure 7 is a cross-sectional view of a diaphragm according to one aspect of the utility model;

[0046] Figure 8 is a cross-sectional view of a diaphragm according to one aspect of the present invention.

[0047] Description of Reference Numerals

[0048] 100: Organic particles

[0049] 10: Protrusion

[0050] 20: Tanibe

[0051] 1: Porous substrate

[0052] 2: Heat-resistant adhesive layer DETAILED DESCRIPTION

[0053] The present invention is described in more detail through the following implementation examples or embodiments, but the following implementation examples or embodiments are only a reference for describing the present invention in detail, and the present invention is not limited thereto and can be implemented in many ways.

[0054] Furthermore, unless otherwise defined, all technical and scientific terms have the same meaning as those generally understood by one of ordinary skill in the art to which the present invention pertains. The terms used in the present invention for illustration are only used to effectively describe specific examples and are not intended to limit the present invention.

[0055] Furthermore, the singular form used in the specification and technical solution may be intended to include the plural form unless otherwise specified in the text.

[0056] Furthermore, when it is mentioned that a part “includes” a certain constituent element, unless there is any particular description to the contrary, it does not exclude other constituent elements but indicates that other constituent elements may be included.

[0057] One aspect of the utility model provides a secondary battery separator, comprising: a porous substrate having a thickness of 3 to 50 μm; a heat-resistant adhesive layer disposed on at least one side of the porous substrate and having a thickness of more than 0 μm and less than 2 μm;

[0058] The heat-resistant adhesive layer includes inorganic particles; and a binder component including organic particles having a plurality of protrusion parts and a plurality of valley parts, wherein the average particle diameter D50 of the organic particles is 0.1 to 1.5 μm.

[0059] As an example, Figure 7 As shown in FIG. 1 , the porous substrate 1 and the heat-resistant adhesive layer 2 may be stacked in sequence. Figure 8 As shown, the heat-resistant adhesive layer 2, the porous substrate 1 and the heat-resistant 2 may be stacked in this order. Figure 7 and Figure 8 The stacked structure of the secondary battery separator of the present invention is exemplified, but is not limited thereto.

[0060] In the present invention, the organic particles 100 may be polymer particles, such as Figure 1 and Figure 2As shown, it may be formed with a plurality of protrusions (protrusion part) 10 and a plurality of valley parts (valley part) 20. As an example, the organic particles may be aggregates of a plurality of primary particles that are polymerized and condensed with each other through surface melting, i.e., secondary particles. The plurality of protrusions 10 and the plurality of valley parts 20 may be formed by the condensation of the primary particles. The adhesive particles in the form of secondary particles may refer to a particle form having a plurality of protrusions corresponding to a portion of the primary particles, and a valley (valley) or a shrunken cavity (shrinked cavity) formed between the protrusions and the protrusions. For example, it refers to a plurality of protrusions (bump parts) of primary particle forms including three or more, four or more, five or more, six or more, or eight or more protrusions on the surface of the organic particles, and a plurality of valley parts (valley parts) or shrunken parts formed between the protrusions.

[0061] Alternatively, the primary particles may have a plurality of protrusions and a plurality of valleys on the surface.

[0062] The protrusions and valleys of the organic particles may be irregular in size and shape. The term "irregular" means substantially non-linear, substantially non-uniform, or substantially asymmetric. The term "protrusion" means a portion protruding from the surface of the particle. Figure 1 and Figure 2 The “valley or concave portion” refers to a concave portion (concavity) on the surface of the particle, which is formed by the height difference between the plurality of protrusions formed radially from the center of the organic particle, or a concave portion formed between protrusions, Figure 1 and Figure 2 In the figure, 20 is used to indicate it.

[0063] In the present invention, "Dn" (n is a real number) refers to the diameter of particles whose cumulative fraction based on volume is equivalent to n%. For example, "D50" refers to the diameter of particles whose cumulative fraction based on volume is equivalent to 50%. "D90" refers to the diameter of particles whose cumulative fraction based on volume is equivalent to 90%. "D10" refers to the diameter of particles whose cumulative fraction based on volume is equivalent to 10%. The Dn can be derived from the particle size distribution results obtained by collecting samples of the particles to be measured according to ISO 13320-1 specifications and analyzing them using a particle size analyzer S3500 of Microtrac.

[0064] According to one aspect, the diaphragm of the utility model can be a diaphragm including a porous substrate and a heat-resistant adhesive layer arranged on at least one side of the porous substrate, the heat-resistant adhesive layer containing inorganic particles and organic particles having multiple protrusions (protrusion parts) and multiple valley parts (valley parts), and the average particle size D50 of the organic particles is 0.1 to 1.5 μm.

[0065] The following is a detailed description of each structure of the separator.

[0066] In one implementation example, the porous substrate may be a polyolefin-based porous substrate such as polyethylene and polypropylene, but is not particularly limited, and all porous substrates known as porous substrates for use as separators of electrochemical elements may be used. In one implementation example, the porous substrate may be manufactured into a film or a sheet, but is not particularly limited. As an example, the porous substrate includes polyolefins such as polyethylene and polypropylene, and a multilayer film of two or more layers may be used.

[0067] In one implementation example, the thickness of the porous substrate may be, for example, 1 μm or more, 2 μm or more, 3 μm or more, 4 μm or more, 5 μm or more, or 6 μm or more. The upper limit is not particularly limited, but may be, for example, 100 μm or less, 50 μm or less, 30 μm or less, 20 μm or less, 15 μm or less, 12 μm or less, or a value between these values, and may be 1 to 100 μm without limitation, and may be 3 to 50 μm, 5 to 20 μm, or 5 to 15 μm in order to realize a high-capacity battery.

[0068] In one implementation example, the heat-resistant adhesive layer can be a porous layer in which inorganic particles are connected and fixed by adhesive components to form pores, and the organic particles are connected and fixed to the inorganic particles or adhesive components to form pores. In one implementation example, the heat-resistant adhesive layer is arranged on one or both sides of the porous substrate, and can be coated to an area fraction of 60% or more, 70% or more, 80% or more, or 90% or more based on the entire surface of the porous substrate, preferably 100% except for some defective cases.

[0069] As an implementation example, the inorganic particles are added to improve the heat resistance of the diaphragm, and their types are not particularly limited. According to non-limiting examples, the inorganic particles may include one or more of metal hydroxides, metal oxides, metal nitrides and metal carbides. For example, it may include any one or more of the group consisting of SiO2, SiC, MgO, Y2O3, Al2O3, CeO2, CaO, ZnO, SrTiO3, ZrO2, TiO2 and AlO(OH), but not limited thereto. In order to improve the stability of the battery, the inorganic particles are more preferably metal hydroxide particles such as boehmite, pseudo-boehmite, aluminum hydroxide and magnesium hydroxide, but not limited thereto.

[0070] As an implementation example, when boehmite is used as the inorganic particle, the specific surface area (BET) of the boehmite may be 10 m 2 / g or above or 15m 2 / g or more, but is not particularly limited thereto.

[0071] In one implementation example, the D50 of the inorganic particles may be greater than 0 μm, greater than 0.05 μm, greater than 0.1 μm, less than 5 μm, less than 3 μm, less than 2 μm, less than 1 μm, less than 0.5 μm, or a value between the above values. For example, it may be greater than 0 μm and less than 5 μm, or greater than 0 μm and less than 3 μm, greater than 0.05 μm and less than 2 μm, greater than 0.1 μm and less than 1 μm, or greater than 0.1 μm and less than 0.5 μm.

[0072] The method for preparing inorganic particles that meet the D50 numerical range of the implementation example is not particularly limited, but as a non-limiting example, individual inorganic particles that meet the D50 numerical range can be prepared, or different inorganic particles with D50 can be mixed to prepare mixed inorganic particles that meet the D50 numerical range.

[0073] The heat-resistant adhesive layer of an implementation example includes the organic particles having multiple protrusion parts and multiple valley parts as adhesive components, and the average particle size D50 of the organic particles is 0.1 to 1.5 μm. In the case of a thin film, specifically, the adhesion between the electrode is still excellent when the thickness is 50 μm or less. Compared with the permeability of the porous substrate itself, the increase in permeability after forming the heat-resistant adhesive layer is still small, and no adhesion occurs, so that the problem of assembling the battery can be solved. In addition, a separator with better adhesion to the electrode than using generally spherical organic particles can be provided.

[0074] Next, the organic particles that contribute most to the electrode bonding strength among the binder components in the heat-resistant binder layer of this embodiment will be described in detail.

[0075] In the present invention, the organic particles may be secondary particles in the form of primary particles condensed by surface melting or single particles having a plurality of protrusions protruding convexly and a plurality of depressions or valleys between the protrusions.

[0076] The organic particles are not particularly limited, but may be, for example, "organic particles in the form of secondary particles" having a D50 particle size of 0.1 to 1.5 μm, 0.2 to 1.5 μm, or 0.3 to 1 μm. Typical forms of the binder particles in the form of secondary particles are as follows: Figure 1 As shown, it may refer to a plurality of polymerized primary particles that melt with each other, for example, the surface melts to agglomerate, so that the primary particles protrude on the surface of the agglomerate and valleys are formed between the primary particles. As another example, it may refer to a particle having three or more protruding protrusions and multiple valleys or multiple shrunken cavities between the protrusions in one particle even without agglomeration. For example, it may refer to a particle having three or more, four or more, five or more, or six or more protruding protrusions and multiple valleys or multiple shrunken cavities between the protrusions formed on the surface of an organic particle.

[0077] The organic particles of the present invention having the size and shape are as follows Figure 5 Compared with spherical organic particles of the morphology shown, even if the content is relatively small, the adhesion between the electrode can be sufficiently improved and the air permeability and anti-blocking property can be significantly improved.

[0078] And regarding the average particle size (D50) of the organic particles, there is no special restriction on the premise of having the above-mentioned morphology, but for example, it can be less than 1.5μm, less than 1μm, less than 0.5μm, more than 0.1μm, more than 0.3μm, more than 0.5μm, preferably, it can be 0.1 to 1.5μm, or it can be 0.2 to 1.0μm.

[0079] In the case of the average particle size range, the adhesion effect with the inorganic particles is better achieved and the adhesion with the electrode is significantly improved. In particular, in the case of a size of 0.1 to 1.5 μm, the adhesion between the adhesive layers during transfer or lamination, or the adhesion of the adhesive to other parts in contact with the heat-resistant adhesive layer, resulting in the detachment of the adhesive layer on the inorganic particle layer, is significantly reduced, the adhesion with the electrode is also significantly increased, and it can be made into a thin film, so it is better.

[0080] In one implementation example, regarding the particle size distribution of the organic particles, the D10 / D90 value may be greater than 0.3, greater than 0.4, less than 0.9, less than 0.8, or a value between the above values. Alternatively, it may be 0.3 to 0.9, or 0.4 to 0.8. When the particle size distribution range of the organic particles is met, the content of the organic particles used to ensure the electrode adhesion can be further reduced, thereby being more conducive to ensuring air permeability and anti-adhesion, and therefore preferred, but not necessarily limited thereto.

[0081] In one implementation example, for the organic particles, when the ratio of the average particle size of the organic particles to the average particle size (D50) of the inorganic particles is 0.5 or more, 0.6 or more, 0.7 or more, 2.5 or less, 1.5 or less, 1.3 or less, 1.0 or less, or a value between the above values, the content of organic particles flowing into the surface unevenness or pores of the inorganic particle layer can be further reduced, thereby being more conducive to ensuring air permeability and anti-adhesion, and therefore preferred, but not necessarily limited thereto. Preferably, the ratio of the average diameter of the organic particles / the average diameter of the inorganic particles can be 0.5 to 2.5, 0.5 to 1.5, 0.6 to 1.3, or 0.7 to 1.0.

[0082] In one implementation example, in order to provide a separator having excellent electrode adhesion, anti-adhesion and air permeability even when the thickness of the heat-resistant adhesive layer is thin, the heat-resistant adhesive layer may contain 50% by weight or more, 60% by weight or more, 70% by weight or more, 80% by weight or more, 90% by weight or more, 95% by weight or more, 99% by weight or more, or 100% of the organic particles based on the total weight of the adhesive component. The more the content of the organic particles in the secondary particle form, the more conducive it is to achieve the purpose of the utility model, so there is no particular restriction on the upper limit of the content.

[0083] The organic particles are Figure 1 As shown, it has a specific morphology as defined above, so compared with the polymer that is the same as the organic particles but has a morphology as shown Figure 5 The spherical or round shape without valleys can have relatively significant electrode adhesion, air permeability, anti-adhesion and other excellent physical properties. Therefore, the composition of the organic particles of the utility model is not particularly limited, as long as it is the composition of organic particles commonly used in the corresponding technical field to improve electrode adhesion.

[0084] For example, the organic particles may be made of crosslinked or uncrosslinked particle-type acrylic polymer or fluorine-based polymer, or may be of a core-shell structure. The core-shell structured particle-type acrylic polymer may be, for example, a core rubber or crosslinked particle surface including acrylic monomers and other comonomers and crosslinking agents as required to polymerize, but is not particularly limited.

[0085] The organic particles of the specific form according to the implementation example are preferably used because of their structural characteristics, so that a small amount can significantly improve the electrode adhesion, and the case of having a high glass transition temperature can further improve the anti-adhesion property. In this case, the glass transition temperature (Tg) of the organic particles can be above 50°C, above 60°C, below 90°C, below 80°C, below 70°C, or a value between these values, for example, 50 to 90°C, 55 to 75°C, or 60 to 70°C, but is not limited thereto.

[0086] In one implementation example, the heat-resistant adhesive layer may selectively further include other components such as lubricants and surfactants that are known to be added to the electrode adhesive organic layer of the separator in the corresponding technical field, but is not particularly limited.

[0087] In one implementation example, the heat-resistant adhesive layer may include an organic adhesive in addition to the organic particles as an adhesive component. The organic adhesive is not particularly limited as long as it can connect and fix the inorganic particles in the heat-resistant adhesive layer. As an example, the organic adhesive may be in a particle form or a non-particle form. In the case of a particle form, it may be a particle having a form different from the organic particles having a plurality of protrusion parts and a plurality of valley parts. In addition, the organic adhesive may be an aqueous latex.

[0088] As a non-limiting example, the organic binder may include an acrylic polymer selected from polymethylmethacrylate, polybutylacrylate, polyacrylonitrile, etc.; (3-aminopropyl)triethoxysilane, (3-aminopropyl)trimethoxysilane, (3-glycidyloxypropyl)trimethoxysilane and their oligomers or silane compounds prepared therefrom; styrene butadiene rubber; carboxylmethylcellulose (CMC); polyvinylidene fluoride (PVDF); any one or two or more selected from the group consisting of polyvinyl fluoride (PVdF); polyvinyl pyrrolidone (PVP); and polyvinylacetate (PVAc); etc., but the present invention is not limited thereto.

[0089] In a specific implementation example, the heat-resistant adhesive layer may include 30 to 85 wt % of inorganic particles, 10 to 60 wt % of organic particles, and 1 to 15 wt % of organic binder based on the total weight of the heat-resistant adhesive layer, but is not particularly limited.

[0090] In one implementation example, the heat-resistant adhesive layer may contain 30% by weight or more, 35% by weight or more, 40% by weight or more, 85% by weight or less, 80% by weight or less, or a value between the above values, based on the total weight of the heat-resistant adhesive layer, and specifically may contain 30 to 85% by weight or 40 to 80% by weight of inorganic particles. Including inorganic particles within the content range in the one implementation example can further improve the heat resistance of the separator, but is not particularly limited.

[0091] In one implementation example, the heat-resistant adhesive layer may contain 10% by weight or more, 15% by weight or more, 20% by weight or more, 60% by weight or less, 55% by weight or less, 50% by weight or less, or values ​​between the above values, based on the total weight of the heat-resistant adhesive layer, and specifically may contain 10 to 60% by weight, 15 to 55% by weight, or 20 to 50% by weight. Including the organic particles in the content range in the one implementation example can further improve electrode adhesion, anti-blocking properties, or air permeability, but is not particularly limited.

[0092] In one implementation example, the heat-resistant adhesive layer may contain an organic binder in an amount of 1 wt %, 2 wt %, 3 wt %, 15 wt %, 12 wt %, 10 wt %, or a value between the above values, based on the total weight of the heat-resistant adhesive layer, specifically 1 to 15 wt %, 2 to 12 wt %, 3 to 10 wt %. In the case where the organic binder is included in the content range in the one implementation example, the inorganic particles in the diaphragm can be more firmly connected and fixed, but is not particularly limited.

[0093] In one implementation example, the heat-resistant adhesive layer may selectively include, as adhesive components, the organic adhesive and the organic particles having a plurality of protrusion parts and a plurality of valley parts, and may also include any adhesive known in the corresponding technical field without particular limitation.

[0094] In one implementation example, the heat-resistant adhesive layer can be arranged on one side or both sides of the porous substrate. When the heat-resistant adhesive layer is arranged on both sides of the porous substrate, the thickness of the heat-resistant adhesive layer arranged on one side and the other side may be the same or different. In one implementation example, the thickness of the heat-resistant adhesive layer arranged on one side of the porous substrate can be more than 0 μm, more than 0.1 μm, more than 0.2 μm, more than 0.3 μm, more than 0.4 μm, more than 0.5 μm, less than 5 μm, less than 4 μm, less than 3 μm, less than 2.5 μm, less than 2 μm, or a value between the above values. The thickness of the heat-resistant adhesive layer can be more than 0 μm and less than 5 μm. In order to realize a high-capacity battery, specifically, it can be more than 0 μm and less than 3 μm, or more than 0 μm and less than 2.5 μm.

[0095] The heat-resistant adhesive layer is configured on the porous substrate by utilizing all methods known in the corresponding technical field. The conventional manufacturing method is sufficient, and is not particularly limited. As a non-limiting example, after the mixture of inorganic particles, organic binder and organic particles is added with water and stirred to be prepared into a heat-resistant adhesive layer slurry, the prepared slurry is coated on one or both sides of the porous substrate by slot die coating, roller coating, spin coating, dip coating, bar coating, die coating, slit coating and inkjet printing, or a combination thereof, to form a heat-resistant adhesive layer on the porous substrate.

[0096] The separator according to the above-described implementation example can have excellent electrode adhesiveness, anti-blocking property, or air permeability even in a thin thickness.

[0097] In one implementation example, the separator may be a separator laminated on a carbon sheet having a thickness of 200 μm with the adhesive layer of the separator facing the carbon sheet, and then bonded by pressing at 80°C and 20 MPa for 30 seconds using a hot press, and the electrode adhesion measured by peeling 180° using a UTM device according to ASTM D 903 is 1.5 gf / 15 mm or more, 2.0 gf / 15 mm or more, 2.5 gf / 15 mm or more, or 3 gf / 15 mm or more. Alternatively, the separator may be 1.5 gf / 15 mm to 4.0 gf / 15 mm, or 2.0 to 4.0 gf / 15 mm.

[0098] According to the implementation example, even if a small amount of organic particles having the above-mentioned morphology and a high glass transition temperature are used to apply thinly or the coating area is insufficient, the distribution is good. Therefore, when coated on an inorganic particle layer, sufficient electrode adhesion can be ensured while improving anti-adhesion properties, which is more preferred.

[0099] For example, a porous substrate and a heat-resistant adhesive layer are sequentially stacked in a manner such that the adhesive layers face each other, and then pressed at a temperature of 60°C and a pressure of 7.5 MPa for 1 hour. After that, the bonded portion is peeled off, and SEM is used to confirm whether a portion or all of the adhesive layer is peeled off to cause adhesion between the surfaces of the separators. In this case, the membrane can have excellent anti-adhesion properties without the phenomenon of the adhesive layer being separated from each other's separator portions, i.e., adhesion.

[0100] The air permeability change (ΔG) of the separator of one implementation example expressed by the following formula may be 100 sec / 100 cc or less, 95 sec / 100 cc or less, or 90 sec / 100 cc or less.

[0101] △G=G1-G2

[0102] In the above formula, G1 is the Gurley permeability (sec / 100cc) of the separator having heat-resistant adhesive layers laminated on both sides of the porous substrate, and G2 is the Gurley permeability of the porous substrate itself. The Gurley permeability is measured using a Densometer produced by Toyoseiki Co., Ltd. in accordance with ASTM D 726.

[0103] The separator according to an implementation example may be excellent in two or more of electrode adhesion, anti-adhesion and air permeability, and more preferably, may be excellent in electrode adhesion, anti-adhesion and air permeability.

[0104] Another implementation example provides an electrochemical element including the diaphragm. The electrochemical element may be an energy storage device, which is not particularly limited, but a lithium secondary battery may be cited as a non-limiting example. The lithium secondary battery is well known and its structure is also known, so it is not described in detail in the present utility model.

[0105] According to an implementation example, a lithium secondary battery may be a battery including the above-mentioned separator between a positive electrode and a negative electrode. Here, the positive electrode and the negative electrode may be used without restriction as long as they are positive electrodes and negative electrodes commonly used in lithium secondary batteries.

[0106] The present invention is described in more detail below based on the following embodiments and comparative examples. However, the following embodiments and comparative examples are only used to illustrate the present invention in more detail, and the present invention is not limited to the following embodiments and comparative examples.

[0107] The following are the methods for measuring the physical properties of the separator.

[0108] 1. Electrode Adhesion

[0109] The separator was stacked on a 200 μm thick carbon sheet (TOYO Tanso Korea, PF-20HP) with the heat-resistant adhesive layer of the separator facing the carbon sheet, and then pressed at 80°C and 20 MPa for 30 seconds using a hot press, and then the electrode adhesion was measured by peeling 180° using the UTM equipment of INSTRON according to ASTM D903. The case where the adhesion of the heat-resistant adhesive layer of the separator was too low to be peeled even using the UTM equipment was rated as "unmeasurable".

[0110] 2. Change in air permeability

[0111] The air permeability change ΔG is calculated as follows.

[0112] △G=G1-G2

[0113] In the above formula, G1 is the Gurley permeability (seconds / 100cc) of the separator with heat-resistant adhesive layers laminated on both sides of the porous substrate, and G2 is the Gurley permeability of the porous substrate itself. The Gurley permeability is measured using a Densometer of Toyoseiki Co., Ltd. according to ASTM D 726 specifications, and the time required for 100cc of air to pass through a separator with an area of ​​1 square inch is recorded in seconds. The unit is seconds / 100cc.

[0114] 3. Anti-blocking

[0115] After arranging the two diaphragms stacked with the porous substrate and the heat-resistant adhesive layer so that the heat-resistant adhesive layers face each other, they are pressed at a temperature of 60°C and a pressure of 7.5MPa for 1 hour. Afterwards, the adhesive layers are evaluated according to ASTM D 903 to see whether they are partially or completely peeled off when peeled off 180°. Even if part of the peeling occurs, it is considered that adhesion has occurred. If no peeling occurs and the adhesive layer is separated in its original state, it is considered that no adhesion has occurred. Confirm whether adhesion has occurred by SEM. If adhesion is confirmed by SEM, it is rated as 'NG', and if adhesion is not confirmed, it is rated as 'OK'.

[0116] 4. Average particle size measurement method

[0117] The average particle size (D50), D10, and D90 were measured using a particle size analyzer S3500 manufactured by Microtrac according to ISO 13320-1.

[0118] 5. Glass transition temperature

[0119] The glass transition temperature was measured as follows: using a DSC device (model name: Q200) from TA Corporation, the temperature was raised from -50°C to 300°C at a heating rate of 20°C / min in a nitrogen atmosphere. At this time, the measurement was performed by heating twice (first run, second run, cooling).

[0120] [Example 1]

[0121] 1) Preparation of slurry for heat-resistant adhesive layer

[0122] 35 wt % of acrylic latex (acrylic latex obtained by polymerizing methyl methacrylate and butyl methacrylate) having an average particle size (D50) of 550 nm and a glass transition temperature (Tg) of 65° C. was used as Figure 1 The organic particles of the form shown, 60% by weight of boehmite particles (Nabaltec, Apyral AOH60) with a D50 of 600 nm as inorganic particles, and 5% by weight of a water-soluble acrylic adhesive (Ashland, PVP K120) as an organic adhesive were added to water so that the solid content was 40% by weight and stirred to prepare a uniformly mixed slurry for a heat-resistant adhesive layer. Here, the D10 / D90 of the organic particles was 0.57.

[0123] 2) Manufacturing of diaphragms

[0124] The heat-resistant adhesive layer slurry was applied to both sides of a polyolefin porous substrate (ENPASS, SK innovation) with a Gurley transmittance of 125 seconds / 100cc and a thickness of 8.5 μm using a slot die coating die, and then dried in a dryer maintained at 40°C and wound into a roll form. At this time, the thickness of each heat-resistant adhesive layer was 2 μm and the total thickness of the separator was 12.5 μm. Figure 3 The surface photographs of the adhesive layer are included, and the physical properties thereof are described in Table 1.

[0125] [Example 2]

[0126] The separator was manufactured under the same conditions as in Example 1 except that 40% by weight of organic particles with a D50 of 400 nm and a glass transition temperature (Tg) of 65°C, 55% by weight of boehmite particles with a D50 of 600 nm were used as inorganic particles, and 5% by weight of a water-soluble acrylic polymer was used as an organic binder when preparing the slurry for the heat-resistant adhesive layer. Here, the D10 / D90 of the organic particles was 0.45. The results are included in Table 1.

[0127] [Example 3]

[0128] A separator was produced under the same conditions as in Example 1 except that an acrylic latex having a D50 of 1.5 μm and a glass transition temperature (Tg) of 65° C. was used instead of the organic particles of Example 1 and boehmite having a D50 of 1000 nm as inorganic particles was used in the content described in Table 1. The results are shown in Table 1.

[0129] [Example 4]

[0130] A separator was produced under the same conditions as in Example 1 except that an acrylic latex having a D50 of 1 μm and a glass transition temperature (Tg) of 65° C. was used in place of the organic particles of Example 1 according to the content described in Table 1, and boehmite having a D50 of 750 nm was used as an inorganic particle according to the content described in Table 1. The results are shown in Table 1.

[0131] [Example 5]

[0132] The same method as in Example 1 was used, but the heat-resistant adhesive layer slurry was prepared without using a water-soluble acrylic adhesive. That is, 40 wt % of the same acrylic latex as in Example 1 as organic particles and 60 wt % of boehmite particles having a D50 of 600 nm as inorganic particles were added to water so that the solid content was 40 wt % and stirred to prepare a uniformly mixed heat-resistant adhesive layer slurry.

[0133] The other aspects were carried out in the same manner as in Example 1. Table 1 shows the physical properties.

[0134] [Example 6]

[0135] The same conditions as in Example 1 were followed except that an acrylic latex having a D50 of 1.5 μm and a glass transition temperature (Tg) of 65° C. was used in place of the organic particles of Example 1 and boehmite particles having a D50 of 600 nm were used as inorganic particles in the content described in Table 1. The results are shown in Table 1.

[0136] [Comparative Example 1]

[0137] The same method was followed except that the acrylic latex of Example 1 was dissolved in an organic solution and applied when preparing the slurry for the heat-resistant adhesive layer. Figure 4 The results are listed in Table 1.

[0138] [Comparative Example 2]

[0139] Except that the same monomers as in Example 1 were used to prepare the slurry for the heat-resistant adhesive layer, the suspension polymerization was carried out. Figure 5 A separator was manufactured under the same conditions as in Example 1 except that spherical acrylic latex having a D50 of 550 nm and a glass transition temperature (Tg) of 65° C. was added as completely spherical organic binder particles in place of the organic particles in Example 1 at the same content. Figure 5 The results are listed in Table 1.

[0140] [Comparative Example 3]

[0141] The diaphragm was manufactured under the same conditions as in Example 1 except that 45% by weight of acrylic latex with a D50 of 200 nm and a glass transition temperature (Tg) of 65°C was used as completely spherical organic binder particles instead of the organic particles in Example 1, 50% by weight of boehmite particles with a D50 of 600 nm as inorganic particles, and 5% by weight of acrylic polymer as an organic binder. Figure 6 The results are listed in Table 1.

[0142] [Comparative Example 4]

[0143] When preparing the heat-resistant adhesive layer slurry, the following Figure 1 The particles of the morphology shown are organic particles prepared by suspension polymerization of the same monomers as the organic particles of Example 1. Here, a separator was manufactured under the same conditions as in Example 1 except that an acrylic latex having a D50 of 2 μm and a glass transition temperature (Tg) of 65° C. was applied according to the content described in Table 1. The results are shown in Table 1.

[0144] [Comparative Example 5]

[0145] When preparing the heat-resistant adhesive layer slurry, the following Figure 1 The particles of the morphology shown are organic particles prepared by suspension polymerization of the same monomers as the organic particles of Example 1. Here, a separator was manufactured under the same conditions as in Example 1 except that an acrylic latex having a D50 of 5 μm and a glass transition temperature (Tg) of 65° C. was applied according to the content described in Table 1. The results are shown in Table 1.

[0146] Table 1 summarizes the evaluation results of the physical properties of the separators manufactured in the examples and comparative examples of the present invention.

[0147]

Table 1

[0148]

[0149] As can be seen from the results in Table 1 and the accompanying drawings, the heat-resistant adhesive layer is composed of Figure 3 The organic particles are formed in the form of secondary particles including a convex protrusion on the surface and a valley part between the protrusions, and the average diameter of the organic particles meets the range of 0.1 to 1.5 μm, the organic particles use more than 50% by weight of the binder component, and the ratio of the average particle size (D50) of the organic particles to the average particle size (D50) of the inorganic particles meets the range of 0.5 to 1.5. The heat-resistant adhesive layer is well formed on the porous substrate. In addition, it is confirmed that the electrode adhesion meets the range of 1.5 gf / 15mm to 4.0 gf / 15mm, the air permeability change is less than 100 seconds / 100cc, and the physical properties of no adhesion can be simultaneously met.

[0150] In contrast, Comparative Example 1 uses a soluble acrylic polymer such as Figure 4 The pores on the surface are blocked, resulting in poor air permeability and extremely low electrode adhesion.

[0151] Compared with Example 1, see Figure 5 Comparative Example 2 used completely spherical organic binder particles whose circumference was smaller than that of the organic particles based on the same diameter. As a result, the electrode binding force was inferior to that of Example 1 based on the same content.

[0152] The average particle size of the organic binder particles in Comparative Example 3 is too small compared to the average particle size of the inorganic particles. Figure 6 As shown, the organic binder particles are buried between the surface irregularities of the inorganic particles or between the inorganic particles, so the adhesive force is poor.

[0153] Comparative Examples 4 and 5 used the same organic particles as Example 1, with average particle sizes of 2 μm and 5 μm, respectively. It was confirmed that although adhesive force was exerted in this case, the air permeability changed greatly and blocking occurred. In addition, powder fell off after the separator was manufactured.

[0154] As described above, the present invention is described through specific matters and limited embodiments, but this is only provided to help a more comprehensive understanding of the present invention. The present invention is not limited to the above embodiments, and ordinary technicians in the field to which the present invention belongs can make various modifications and variations based on these records.

[0155] Therefore, the present invention should not be limited to the embodiments described above, and the above technical solutions and everything that is equivalent to or has equivalent variations of the technical solutions belong to the scope of the present invention.

Claims

1. A secondary battery separator, characterized in that: include: A porous substrate having a thickness of 3 to 50 μm; as well as a heat-resistant adhesive layer disposed on at least one side of the porous substrate and having a thickness of more than 0 μm and less than 2 μm, Wherein, the heat-resistant adhesive layer comprises: Inorganic particles; and a binder component comprising organic particles having a plurality of protrusions and a plurality of valleys, The organic particles have an average diameter D50 of 0.1 to 1.5 μm.

2. The secondary battery separator according to claim 1, characterized in that: The heat-resistant adhesive layer contains 50 wt % or more of the organic particles based on the total weight of the adhesive component.

3. The secondary battery separator according to claim 1, characterized in that: The heat-resistant adhesive layer further includes an organic binder as the binder component.

4. The secondary battery separator according to claim 3, characterized in that: The heat-resistant adhesive layer includes 30 to 85 wt % of inorganic particles, 10 to 60 wt % of organic particles, and 1 to 15 wt % of an organic binder, based on the total weight of the heat-resistant adhesive layer.

5. The secondary battery separator according to claim 1, characterized in that: The ratio of the average particle size D50 of the organic particles to the average particle size D50 of the inorganic particles is 0.5 to 2.

5.

6. The secondary battery separator according to claim 1, characterized in that: The particle size distribution D10 / D90 of the organic particles is 0.3 to 0.

9.

7. The secondary battery separator according to claim 1, characterized in that: The organic particles have a glass transition temperature Tg of 50 to 90°C.

8. The secondary battery separator according to claim 1, characterized in that: The organic particles are secondary particles formed by mutual aggregation of primary particles through surface melting to form a plurality of protrusions and a plurality of valleys, or are primary particles having a plurality of protrusions and a plurality of valleys on the surface.

9. The secondary battery separator according to claim 1, characterized in that: The secondary battery separator is a secondary battery separator with an electrode adhesion of 1.5 gf / 15 mm to 4.0 gf / 15 mm, wherein the electrode adhesion is measured by laminating the secondary battery separator on a carbon sheet with a thickness of 200 μm with the heat-resistant adhesive layer of the secondary battery separator facing the carbon sheet, and then bonding the carbon sheet by pressing at 80°C and 20 MPa for 30 seconds with a hot press, and then peeling 180° using UTM equipment from INSTRON according to ASTM D 903.

10. The secondary battery separator according to claim 9, characterized in that: The secondary battery separator has an air permeability change ΔG measured by the following formula of 100 seconds / 100 cc or less. △G=G1-G2 In the above formula, G1 is the Gurley permeability of a secondary battery separator having heat-resistant adhesive layers laminated on both sides of a porous substrate, and G2 is the Gurley permeability of the porous substrate itself. The Gurley permeability is measured using an air permeability meter from Toyoseiki Co., Ltd. according to ASTM D 726, and the unit is seconds / 100cc.

11. The secondary battery separator according to claim 10, characterized in that: The secondary battery separator is a secondary battery separator in which two secondary battery separators are arranged so that the adhesive layers face each other, and then pressed at a temperature of 60°C and a pressure of 7.5 MPa for 1 hour. When peeled 180° according to ASTM D 903, the adhesive layers do not adhere to each other and partially or completely peel off, but are separated in their original state without adhesion.

12. An electrochemical element, characterized in that: A secondary battery separator according to any one of claims 1 to 11.